Effect of deferasirox + erythropoietin vs erythropoietin on erythroid response in Low/Int‐1‐risk MDS patients: Results of the phase II KALLISTO trial. (22nd June 2018) - Gattermann, Norbert; Coll, Rosa; Jacobasch, Lutz; Allameddine, Allameddine; Azmon, Amin; DeBonnett, Laurie; Bruederle, Andreas; Jin, Jie; ,
Abstract: Objectives: Erythropoiesis‐stimulating agents (ESAs) remain first‐choice to treat symptomatic anemia and delay transfusion dependence in most patients with lower‐risk myelodysplastic syndromes (MDS) without del(5q). Deferasirox increased erythroid responses in some lower‐risk MDS patients in clinical trials, and adding low‐dose deferasirox to ESA treatment may further improve erythroid response. Methods: KALLISTO (NCT01868477 ) was a randomized, open‐label, multicenter, phase II study. Lower‐risk MDS patients received deferasirox at 10 mg/kg/d (dispersible tablets) or 7 mg/kg/d (film‐coated tablets) plus erythropoietin (n = 11), or erythropoietin alone (n = 12) for 24 weeks. The primary endpoint was the between‐group difference in erythroid response within 12 weeks. Results: Erythroid response occurred in 27.3% of patients receiving deferasirox plus erythropoietin vs 41.7% of patients receiving erythropoietin alone within 12 weeks (difference 14.4%; 95% CI −24.0, 48.16). Within 24 weeks, the hematologic response rate was 27.3% with deferasirox plus erythropoietin vs 50% with erythropoietin alone, and hematologic improvement rates were 45.5% vs 100%. Deferasirox plus erythropoietin was generally well tolerated. Conclusions: In this small pilot study, combining low‐dose deferasirox with erythropoietin did not improve erythroid response. It remains of interest to investigate early chelation approaches with even lower deferasirox doses plus erythropoietin in lower‐risk MDS patients before the onset of transfusion dependence.